2019
DOI: 10.1016/j.cmet.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

LINE1 Derepression in Aged Wild-Type and SIRT6-Deficient Mice Drives Inflammation

Abstract: Graphical Abstract Highlights d SIRT6 KO mice accumulate L1 cDNA, triggering interferon response via cGAS pathway d Wild-type aged mice accumulate L1 cDNA and display type I interferon response d Reverse-transcriptase inhibitors rescue type I interferon response and DNA damage d Reverse-transcriptase inhibitors extend lifespan and improve health of SIRT6 KO mice SUMMARYMice deficient for SIRT6 exhibit a severely shortened lifespan, growth retardation, and highly elevated LINE1 (L1) activity. Here we report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
388
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 364 publications
(414 citation statements)
references
References 55 publications
25
388
1
Order By: Relevance
“…Beyond its ability to enhance DSB repair, a major role of SIRT6 is to repress the expression of ancient retroviral elements (LINE1 or L1) that account for a significant fraction of mammalian genomes . The importance of LINE1 elements in aging as well as in the context of SIRT6 as a promoter of overall genome integrity was bolstered by two recent reports showing that showed that L1 elements become transcriptionally derepressed during aging and that this derepression activates a type‐I interferon (IFN‐I) inflammatory response . The effect can be suppressed by reverse transcriptase (RT) inhibitors to block expansion/reintegration of L1s.…”
Section: Proteomics and The Hallmarks Of Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond its ability to enhance DSB repair, a major role of SIRT6 is to repress the expression of ancient retroviral elements (LINE1 or L1) that account for a significant fraction of mammalian genomes . The importance of LINE1 elements in aging as well as in the context of SIRT6 as a promoter of overall genome integrity was bolstered by two recent reports showing that showed that L1 elements become transcriptionally derepressed during aging and that this derepression activates a type‐I interferon (IFN‐I) inflammatory response . The effect can be suppressed by reverse transcriptase (RT) inhibitors to block expansion/reintegration of L1s.…”
Section: Proteomics and The Hallmarks Of Agingmentioning
confidence: 99%
“…The effect can be suppressed by reverse transcriptase (RT) inhibitors to block expansion/reintegration of L1s. Furthermore, loss of L1 suppression is a major contributor to aging in SIRT6 knockout mice that can be partially rescued by adding RT inhibitors . Upon the loss of SIRT6, the copy number of cytoplasmic L1 species accumulate triggering type‐I interferon response via cGAS/STING pathway.…”
Section: Proteomics and The Hallmarks Of Agingmentioning
confidence: 99%
“…Increased L1 activity results in the accumulation of L1 ‐derived cytosolic DNA from extrachromosomal copies that fail to integrate, which is detected by innate immune systems that recognize cytosolic DNA from invading viruses. This promotes interferon production, contributing to a chronic state of low‐grade inflammation that plays a role in ageing . Somatic L1 activity has been implicated in age‐related pathologies, including neurodegeneration and cancer, and small molecule inhibition of L1 reverse transcriptase activity maintains genome stability .…”
Section: Introductionmentioning
confidence: 98%
“…L1 elements replicate through an RNA transcript that is reverse transcribed, and are capable of re‐integration into the genome, allowing for expansion in their copy numbers if de‐repressed during ageing or genotoxic stress . Importantly, the insertion of additional L1 elements into the genome following their de‐repression induces DNA breaks, and this damage further drives the migration of transcriptional repressors, leading to further de‐repression of other endogenous TEs, initiating a “vicious cycle” that could drive ageing . Increased L1 activity results in the accumulation of L1 ‐derived cytosolic DNA from extrachromosomal copies that fail to integrate, which is detected by innate immune systems that recognize cytosolic DNA from invading viruses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation